Manual of leaf architecture - Ellis, Beth (2009)
Offers a reference for describing, measuring and classifying the foliage of flowering plants. This title presents a system that provides long-needed guidelines for characterizing the organization, shape, venation, and surface features of angiosperm leaves.
1. General leaf definitions -- 2. Leaf characters -- 3. General vein definitions -- 4. Determining vein order -- 5. Vein characters -- 6. General tooth definitions -- 7. Tooth characters
"Published in association with the New York Botanical Garden."
Includes bibliographical references and index
Keywords: Leaves -- Anatomy -- Handbooks, manuals, etc; Leaves -- Morphology -- Handbooks, manuals, etc